The Influence of the Contextual Teaching and Learning (CTL) Learning Model on Students' Critical Thinking Ability in Class VIII Respiratory System Material at SMP Negeri 2 Gunungsari - Umami, Risa; Arizatul Aslamiyah (UNIVERSITAS PGRI MADIUN, 2024)
This research aims to determine whether there is an influence of the Contextual Teaching and Learning (CTL) learning model on students' critical thinking skills in class VIII respiratory system materials at SMP Negeri 2 Gunungsari. The type of research used is Quasi experimental design with a quantitative approach. The population in this study were students in class VIII of SMP Negeri 2 Gunungsari, with the research sample being class VIII A as the experimental class and class VIII B as the control class. The instrument used in this research is test questions in the form of essays. Data analysis was carried out by hypothesis testing (t-test). The results of the research show that the Contextual Teaching and Learning (CTL) learning model on students' critical thinking skills in class VIII respiratory system material at SMP Negeri 2 Gunungsari, with a significant value of 0.000 < 0.005, means that Ho is rejected and Ha is accepted so it can be concluded that there is a significant influence. significant impact on the use of the Contextual Teaching and Learning (CTL) learning model on students' critical thinking abilities.